Elaboration and validation of an ICNP® terminology subset for patients with acute myocardial infarction - Renata Soares Passinho; Cândida Caniçali Primo; Mirian Fioresi; Maria Miriam Lima da Nóbrega; Marcos Antônio Gomes Brandão; Walckiria Garcia Romero (SciELO, 2019)
ABSTRACT Objective: To elaborate a terminological subset for the International Classification for Nursing Practice (ICNP®) for patients with acute myocardial infarction using the Activities of Living Model. Method: A methodological study which followed the guidelines of the International Nursing Council and was based on theoretical framework of the Activities of Living Model for its elaboration. Content validation was performed by 22 nursing specialists. Results: Twenty-two (22) diagnoses and 22 nursing outcomes were elaborated. Of these, 17 nursing diagnosis statements and 17 nursing outcome statements presented Content Validity Index (CVI) ≥ 0.80. Of the 113 elaborated nursing interventions, 42 reached a CVI ≥ 0.80, and 51 interventions made up the terminological subset after the expert suggestions. Conclusion: The ICNP® was suitable for use with the Activities of Living Model, having compatible terms with those used in clinical nursing practice, and valid for construction of the terminological subset for patients with acute myocardial infarction and most likely to facilitate clinical nursing judgment.